(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article covers the stages of determining nonlinear trends in time series, mathematical modeling, finding trend equations using regression methods, and forecasting. In particular, taking into account the complex dynamics of economic processes, the advantages of exponential, logarithmic, and polynomial models are analyzed. The accuracy and error criteria of forecast results are considered through practical examples.